Kimmy Dora kambal sa kiyeme ([s.l.] Spring Films Production, 2009)
Kimmy and Dora are identical twin heiresses who are totally the opposite. Kemmy is smart, sexy and ambitious. Dora is simple, shy and sweet. Kimmy is sharp and brilliant, Dora is mentally challenged. Kimmy is domineering and overpowering bitch. Dora,on the other, is a pushover, Kimmy has an evil streak while Dora is mother Teresa incarnate. Dora idolizes her older sister while Kimmy abhors her younger sister's naivete and carefree life style.In this deliriously hilarious siblings rivalry, the twins battle over the love of their father the affections of a resident office hunk and the control over the Go Dong Hae group of companies, the most successful corporation in the land. A classic case of mistaken identity ensues when Kimmy inadvertently asked for Dora to be kidnapped. the kidnappers wrongly abduct Kimmy instead of Dora. The funniest aswitcheroo in years happen when Dora and Kimmy exchange places and try to resolve their differences as sisters.
DVD
written by Chris Martinez, directed by Joyce Bernal
Eugene Domingo, Dingdong Dantes, Zanjoe Marudo
Keywords: Comedy films; Feature Films